EFEKTIFITAS MODEL PEMBELAJARAN TUTORIAL DALAM BACA KITAB KUNING: (Studi Kasus di Pesantren Al-Bidayah Jember) - Ulum, Nuzzulul (Jurnal Educazione : Jurnal Pendidikan, Pembelajaran dan Bimbingan dan konseling, 2019)
The purpose of this research is to describe how. the effectiveness of the tutorial learning model in reading the Yellow Book at (Pondok Islamic Boarding School Al-Bidayah Tegal Besar-Kaliwates -Jember). This study used a descriptive qualitative research approach with a case study research type with descriptive data analysis techniques. As for data collection techniques using interviews, observation and documentation using purposive sampling in determining research subjects. From the analysis conducted, it can be concluded that effectiveness in the success of learning the yellow book at Al-Bidayah Islamic Boarding School has an important role. For this, the students depend a lot on the role of the ustadz in making policies in order to achieve the learning objectives of the yellow book, both from the aspects of planning, implementation and evaluation. Key Word: Tutorial learning, Kitab Kuning